2016
DOI: 10.2174/1874453201609010060
|View full text |Cite
|
Sign up to set email alerts
|

Current Topics in Avian Conservation Genetics with Special Reference to the Southwestern Willow Flycatcher

Abstract: It is sometimes said that scientists are entitled to their own opinions but not their own set of facts. This suggests that application of the scientific method ought to lead to a single conclusion from a given set of data. However, sometimes scientists have conflicting opinions about which analytical methods are most appropriate or which subsets of existing data are most relevant, resulting in different conclusions. Thus, scientists might actually lay claim to different sets of facts. However, if a contrary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the only authoritative statement on subspecies in North America, the American Ornithologists' Union (1957) Checklist, this subspecies was not accepted, although it had been described nine years earlier (Phillips, 1948). Data sets on mtDNA, amplified fragment length polymorphisms, niche modeling, and song vocalizations supported the AOU's decision to not designate E. t. extimus as a valid subspecies (Zink, 2015;Zink, 2016;see Theimer et al, 2016;Mahoney et al, 2020). Ruegg et al (2021) analyzed variation in 105,000 single nucleotide polymorphisms (SNPs) from 175 individuals and concluded that the subspecies was valid.…”
Section: What Exactly Is a Subspecies?mentioning
confidence: 99%
See 1 more Smart Citation
“…In the only authoritative statement on subspecies in North America, the American Ornithologists' Union (1957) Checklist, this subspecies was not accepted, although it had been described nine years earlier (Phillips, 1948). Data sets on mtDNA, amplified fragment length polymorphisms, niche modeling, and song vocalizations supported the AOU's decision to not designate E. t. extimus as a valid subspecies (Zink, 2015;Zink, 2016;see Theimer et al, 2016;Mahoney et al, 2020). Ruegg et al (2021) analyzed variation in 105,000 single nucleotide polymorphisms (SNPs) from 175 individuals and concluded that the subspecies was valid.…”
Section: What Exactly Is a Subspecies?mentioning
confidence: 99%
“…Its range includes the densely populated area of southern California from Palos Verde Peninsula south to the border with Baja California (and farther south to the end of Baja California Sur, where it becomes relatively common). The validity of the subspecies has been challenged (Zink et al, 2000;Zink et al, 2013;Zink et al, 2016) and defended (McCormack and Maley, 2015), and recent genomics data show that it is not evolutionarily distinct and hence not a valid subspecies (Vaźquez-Miranda et al, 2022). The USFWS has suggested that excluding this habitat has come at a cost of at least $1 billion (Gordon, 2018).…”
Section: Economics and Subspecies: The Cost Of Invalid Subspeciesmentioning
confidence: 99%